Shariah-Based Hospitality, Competitive Advantage and Tourists’ Revisiting Interest on Indonesia Tourism - NASIR, Abdul; WARIDIN, Waridin; ISKANDAR, Deden Dinar; SUSILOWATI, Indah; HIDAYAT, Abas (Journal of Environmental Management and Tourism, 2022)
Along with the increase in tourist destinations, hotels also increase, ranging from cheap to expensive ones. The promotion of the hotel was well done. However, the low quality of service resulted in the hotel losing guests. Excellence in the hospitality promotion sector is part of the hotel industry's success. For Muslim-majority countries, one of the influential factors in hotel selection is the Halal brand. This study aims to investigate the effect of Sharia-based hospitality hotels on competitive advantage and tourists' revisiting interest. This study uses the method of the Structural Equation Model (SEM). There were 140 respondents consisting of guests, staff, and managers of Shariah hotels in West Java, Indonesia. The sampling technique used in this research was purposive sampling. Hypothetical testing results showed that Shariah-based hospitality hotels significantly affect competitive advantage and tourists' revisiting interest. The competitive advantage significantly affects tourists' revisiting interests. Shariah-based hotel hospitality's creativity and innovation create superior competitiveness and foster interest in staying again. Shariah hotel marketing is not just advertising in digital media but also paying attention to customer feedback.